VARIATIONS OF COLIFORM BACTERIA ISOLATED FROM BALI CATTLE CALVES FECES, MARKETED AT BERINGKIT ANIMAL MARKET - Egrina Sonta Bako; Hapsari Mahatmi; Putu Henrywaesa Sudipa; Gede Putra Sanjaya (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Beringkit Animal Market is one of the largest animal markets in Bali. Which is a place for livestock transactions, especially bali cattle calves, which are usually used as breeds. Bali cattle calves need digestive tract microbes such as bacteria to carry out the digestives process. Coliform bacteria are one of the bacteria that play an important role in the digestive tract of bali cattle calves. Coliform bacteria are one of the bacteria that plays an important role in the digestive tract of bali cattle calves. Coliform bacteria which are included in the Enterobacteriaceae group consist of Escherichia coli, Enterobacter sp., Klebsiella sp., and Citrobacter sp. This research aims to determine what variations of Coliform bacteria are found in the feces of bali cattle calves marketed at the Beringkit Animal Market. This research was observational with the number of samples used were 50 fecal samples from 50 bali cattle calves. The samples were isolated on Eosin Methylene Blue Agar (EMBA) media and then tested and identified using the Indole Methyl Voges Proskauer Citrate (IMViC) principles and Blood agar test. The result showed that 82% of samples were positive Coliform. Based on the result, it can be concluded that in the feces of bali cattle calves marketed at the Pasar Hewan Beringkit contain Coliform bacteria consisting of Escherichia coli, Enterobacter sp., Klebsiella sp., and Citrobacter sp. with the highest percentage was Escherichia coli at 58%, followed by Citrobacter sp. at 12% and Enterobacter sp. and klebsiella sp. respectively 6%. It is necessary to count the total number of each bacteria to determine the pathogenicity of the bacteria.